Three new records of Jungermannia species (Hepaticae, Jungermanniales) from Nepal - Pradhan, Nirmala (International Journal of Environment, 2014)
Jungermanniaceae is the largest family of the Order Jungermanniales, which includes three subfamilies viz Jamesonielloideae, Mylioideae and Jungermannideae representing 18 genera and 71 species in Nepal. This paper deals with three new records viz. Jungermannia exertifolia Steph., J. infusca (Mitt.) Steph. and J. pumila With., which were recorded in the year 2010 and 2011 at different elevations (150 to 1300 m) in Chitwan district of central Nepal. These species were observed mostly in the mesic habitats of Sal (Shorea robusta) forest with other tree species like Dalbergia sisoo and Acacia catechue. Jungermannia pumila was recorded in broad leaved deciduous forest at 1275 m of elevation. DOI: http://dx.doi.org/10.3126/ije.v3i1.9945 International Journal of Environment Vol.3(1) 2014: 85-92